DOI: 10.18122/td/1425/boisestate
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Satellite Fusion Methods to Assess Vegetation Phenology in a Semi-Arid Ecosystem

Abstract: leading to desertification, habitat loss, and the spread of invasive species. Modern public satellite imagery is unable to detect fine temporal and spatial changes that occur in drylands. These ecosystems can have rapid phenological changes, and the heterogeneity of the ground cover is unable to be identified at course pixel sizes (e.g. 250 m). We develop a system that uses data from multiple satellites to model finer data to detect phenology in a semi-arid ecosystem, a dryland ecosystem type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…STARFM-a weighted function-based methods that weight the spatial and temporal aspects, thus capable of reconstructing multi-time data that have gaps and then producing images with good spatial and temporal resolution, developed by Gao et al (2006) has been widely used and has shown success in producing synthetic data like Landsat which has good spatial and temporal resolution for identifying phenological events. Similar studies utilizing STARFM have demonstrated promising results in generating images with adequate spatial and temporal resolution, particularly for detecting phenology (Gallagher, 2018;Onojeghuo et al, 2018;Son et al, 2016;Vincent, 2021). In addition, downscaling MODIS and Landsat-8 data can produce a high-quality time-series data since MODIS and Landsat have similar orbital characteristics with only 30-minutes time difference when crossing equator (Hwang et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…STARFM-a weighted function-based methods that weight the spatial and temporal aspects, thus capable of reconstructing multi-time data that have gaps and then producing images with good spatial and temporal resolution, developed by Gao et al (2006) has been widely used and has shown success in producing synthetic data like Landsat which has good spatial and temporal resolution for identifying phenological events. Similar studies utilizing STARFM have demonstrated promising results in generating images with adequate spatial and temporal resolution, particularly for detecting phenology (Gallagher, 2018;Onojeghuo et al, 2018;Son et al, 2016;Vincent, 2021). In addition, downscaling MODIS and Landsat-8 data can produce a high-quality time-series data since MODIS and Landsat have similar orbital characteristics with only 30-minutes time difference when crossing equator (Hwang et al, 2011).…”
Section: Introductionmentioning
confidence: 92%
“…They generally rely on platforms such as MODIS which trade high revisit frequency with spatial and spectral resolution [Iiames, 2010]. Other methods relate the temporal resolution of MODIS with the spatial and spectral qualities of Landsat [Gallagher, 2018]. Yet others 'reconstruct' time-series data by filling gaps between observations or by fitting mathematical functions to the observations [Zhou et al, 2016].…”
Section: Phenology and Time-seriesmentioning
confidence: 99%
“…Known spectral endmembers ('pure' pixels, either from known locations in the images, or a reference signal) can then inform unmixing of the pixel into its likely constituents. This process has been used with remarkable success, even in shrub-steppe environments [Poley, 2017] It may not be possible to pick a singular date that can minimize confusion between all classes since phenologies of semi-arid vegetation can be disparate [Gallagher, 2018].…”
Section: Phenology and Time-seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine-learning techniques within GEE can be leveraged to improve the accuracy of species classification by finding trends in remotely sensed data (Gallagher, 2018). Random forest (RF) is an ensemble machine learning algorithm that can be used to take training data and create either a classification or regression model (Belgiu & Drăgu, 2016;Pavlov, 2019).…”
Section: Google Earth Engine For Classificationmentioning
confidence: 99%